Comparative study of airborne microbial burden in the vicinity of two landfill sites in mumbai, india. - NEERAJ S. PATIL,; UMESH B. KAKDE, (International Journal of Pharma and Bio Sciences, 2017)
The municipal landfills are favorable sites for growth of microorganisms because of availability of organic matter. If these landfills are insanitary and situated in densely populated areas they may cause various diseases such as, hypersensitive pneumonitis, bronchitis, chronic airway inflammation etc. Hence, regular monitoring of microorganisms in the vicinity of such places is very important. These studies are also useful to decide the control strategies in order to protect the environment. The present study was aimed to investigate microbial bioaerosol concentrations in the vicinity of two landfill sites of Mumbai. The concentration of total heterotrophic bacteria in the vicinity of landfill sites was maximum in monsoon season (1133 cfu/m3- 2155 cfu/m3). While minimum recorded during summer season (153 cfu/m3 - 221 cfu/m3). Staphylococci and Actinomycetes concentrations wereregistered maximum during monsoon (178 cfu/m3 - 240 cfu/m3) while minimum during winter season (28 cfu/m3 - 36 cfu/m3). No bacteria free month recorded at both the selected dumping sites during the entire period of investigation